Silver containing sorbents: Physicochemical and biological properties; Resource-Efficient Technologies; Vol. 2, Iss. 2 - Rachkovskaya L. N.; Popova T. V.; Letyagin A. Yu; Tolstikova T. G.; Korolyov M. A.; Bogdanchikova N.; Pestryakov A. N. Aleksey Nikolaevich; Kotlyarova A. A.; Burmistrov V.; Konenkov V. I. (2016, 2016)
Title screen